"Modern Methods of Teaching English" (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article explores contemporary methods for teaching English, focusing on innovative approaches that enhance language acquisition and learner engagement. By examining the integration of technology, communicative language teaching (CLT), task-based learning (TBL), and content and language integrated learning (CLIL), this study aims to provide educators with effective strategies to improve English proficiency among students. The analysis includes a discussion of the benefits and challenges associated with each method, offering practical recommendations for implementation in various educational contexts.